Between socialists and socialists: the concept of socialism for José Ignacio de Abreu e Lima, 1855 (Ágora Journal, 2024)
O Socialismo from José Ignacio de Abreu e Lima was published at Recife in 1855. The author were already knowed for his written activities at Colombia, where was agratiated with generalship also for his text production in service of Bolívar’s regime, at Rio de Janeiro, when wroted newspapers and history’s books, and at Pernambuco, where he continues his editor’s job which would earn him a life sentence after the failure of the Praieira Insurrection from 1848. This article analyzes how Abreu e Lima develops in Socialismo a philosophy of History in which he elaborates on the civilizatory need for institutional transformations for Brazil based on a very particular instrumentalization of the socialista ideology that had dominated some of Recife’s main printed matter in the previous decade, ideology of which he was one of the main critics and a vigorous print scene of which he was one of the most active editors.
Keywords: Abreu e Lima; editors; socialism.